2015
DOI: 10.1007/s13596-014-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Screening of acetylcholinesterase inhibitors in herbal medicines

Abstract: The pathogenesis of Alzheimer's disease (AD) has been linked to a deficiency in the brain neurotransmitter acetylcholine. Subsequently, acetylcholinesterase (AChE) inhibitors were used for the treatment of mild to moderate AD. The goal of this study was determine the candidate therapeutic herbal medicines on AD through AChE inhibition. In the present study, the AChE inhibitory effects of 255 herbal medicines were evaluated using an AChE assay. 14 herbal medicines increased the AChE activity but 8 herbal medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…AD influences memory and other features of human mind and is characterized by the loss of activities referring to the acetylcholine in the cerebral cortex. Noteworthy, most of the AChE inhibitors such as galanthamine were originally isolated from plants (56). Furthermore, it has been demonstrated that TYR might be related to the damaged neurons typical for another progressive neurological disorder, Parkinson's disease (57).…”
Section: Discussionmentioning
confidence: 99%
“…AD influences memory and other features of human mind and is characterized by the loss of activities referring to the acetylcholine in the cerebral cortex. Noteworthy, most of the AChE inhibitors such as galanthamine were originally isolated from plants (56). Furthermore, it has been demonstrated that TYR might be related to the damaged neurons typical for another progressive neurological disorder, Parkinson's disease (57).…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used treatment against Alzheimer 's disease is the inhibition of acetylcholinesterase (AChE), the enzyme that hydrolyses acetylcholine . Most of the AchE inhibitors such as galanthamine were originally isolated from plants, indicating that herbal medicines are a good source for the search of novel AchE inhibitors . Also, it has been proposed that tyrosinase might be linked with damaged neurons typical for another progressive neurological disease, Parkinson 's disease, pointing to tyrosinase inhibitors as potential medications …”
Section: Resultsmentioning
confidence: 99%
“…[30] Most of the AchE inhibitors such as galanthamine were originally isolated from plants, indicating that herbal medicines are a good source for the search of novel AchE inhibitors. [31] Also, it has been proposed that tyrosinase might be linked with damaged neurons typical for another progressive neurological disease, Parkinson's disease, pointing to tyrosinase inhibitors as potential medications. [9] In a previous work, [4] our group reported moderate neuroprotective activity of V. jacquinii and V. teucrium extracts on human neuroblastoma SH-SY5Y cell line by increasing cell survival in cells stressed with sodium nitroprusside and H 2 O 2 , compared to the nonstressed cells.…”
Section: Evaluation Of Antineurodegenerative Activitymentioning
confidence: 99%